IMPROVING STUDENTS’ MONOLOGIC SPEECH THROUGH TEACHING COMPLEX SYNTACTIC UNITS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The article investigates the decisive role of complex syntactic wholes (CSU) in the development of advanced monologic speech proficiency in EFL/ESL learners. Drawing on discourse linguistics, second-language acquisition research and communicative methodology, the study demonstrates that systematic, discourse-oriented instruction in extended syntactic constructions (syntactic periods, multiple clause embedding, subordination chains, non-finite constructions, and parenthetical insertions) combined with explicit training in cohesion, coherence mechanisms, macro-structural organization and graduated monologic tasks produces statistically significant and qualitatively dramatic improvements in monologue length, fluency, syntactic complexity, textual cohesion, rhetorical effectiveness and overall autonomy of spoken production. The findings reposition complex syntactic training from a peripheral grammatical concern to a core component of advanced oral proficiency development and provide clear evidence-based guidelines for redesigning speaking curricula at B2–C1+ levels.